Hubungan antara Pengetahuan dan Sikap terhadap Penggunaan Kuas di Kalangan Penjual Makanan - Muthia, Syadza; Nurohmi, Susi; Rahadiyanti, Ayu; Fathimah, Fathimah (Journal of Islamic Nutrition, 2018)
The rise of issues regarding the circulation of brush bristle in Indonesia makes the Muslim community need to be careful in selecting products. The objective is to know the correlation between knowledge and attitude to use material brush among food vendors. Data analysis using eta-test to comparation of data analyze. The type of this research is the descriptive-quantitative with cross-sectional approach. The population of this study are 68 food sellers who use brushes in Bogor. The laboratory test used the Fourier Transform Infrared Spectroscopy Analysis (FTIR) to prove that the brush used by food vendors contain an element of pig. About 72.1% of respondents knowledge level is adequate and 69.1% of respondents attitude level is good or positive. Spectroscopic analysis of FTIR-ATR showed that the results obtained did not indicate the presence of pig compounds in each brush sample. The respondents knowledge level is mostly in the adequate category, and the respondents attitude level is mostly in the good category.